2015
DOI: 10.1016/j.jnucmat.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrogen peroxide on uranium oxide films on 316L stainless steel

Abstract: h i g h l i g h t sThe first report of the presence of both UO 2 and polymeric UO 2 2+ in the same electrodeposited U oxide sample.The action of H 2 O 2 on electrodeposited U oxides is described using corrosion based concepts.Electrodeposited U oxide freely dissolves at hydrogen peroxide concentrations <100 lmol dm À3 .At [H 2 O 2 ] > 0.1 mmol dm À3 dissolution is inhibited by formation of a studtite passivation layer. At [H 2 O 2 ] P 1 mol dm À3 studtite formation competes with uranyl-peroxide complex formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…5 The selection of stainless steel in the nuclear industry is based on a combination of high radiation stability and excellent corrosion resistance, the latter afforded by the spontaneous formation of a nanometer-scale passivating Cr-oxide layer at the steel surface. 6 It has been assumed that deposited radioactivity becomes bound to/impregnated within this passive layer during the accumulation process, 7,8 although these phenomena have not been fully demonstrated. However, to make informed decisions regarding the design and optimization of effective decontamination treatments for these materials, an understanding of the principal chemical interactions driving radionuclide uptake onto or into the steel is critical.…”
Section: Introductionmentioning
confidence: 99%
“…5 The selection of stainless steel in the nuclear industry is based on a combination of high radiation stability and excellent corrosion resistance, the latter afforded by the spontaneous formation of a nanometer-scale passivating Cr-oxide layer at the steel surface. 6 It has been assumed that deposited radioactivity becomes bound to/impregnated within this passive layer during the accumulation process, 7,8 although these phenomena have not been fully demonstrated. However, to make informed decisions regarding the design and optimization of effective decontamination treatments for these materials, an understanding of the principal chemical interactions driving radionuclide uptake onto or into the steel is critical.…”
Section: Introductionmentioning
confidence: 99%
“…UO 2 2+ could be reduced to lower valence (U 4+ ) at a certain potential 53,54 . It meant that UO 2 2+ was reduced to UO 2 at the negative electrode, then reacted with H 2 O 2 (reduction of the dissolved oxygen) on the negative electrode to form (UO 2 )O 2 ·4H 2 O 55,56 . During CP‐AO electrosorption, UO 2 2+ was electrochemically reduced to UO 2 after it combined with the amidoxime group, then UO 2 reacted with dissolved oxygen in the solution and oxygen generated by the anode reaction to form UO 3 ·2H 2 O 57 .…”
Section: Resultsmentioning
confidence: 99%
“…This process has been studied extensively over many decades and it has been found that H 2 O 2 is the radiolytic oxidant that dominates the oxidation process under conditions relevant for the safety assessment of a deep geological repository for the spent nuclear fuel. Oxidation of UO 2 by H 2 O 2 is rather complicated mainly for two reasons: (1) the oxidation process contains multiple elementary reaction steps, and (2) the redox property of the UO 2 matrix is strongly dependent on the composition.…”
Section: Introductionmentioning
confidence: 99%